E-voting mobile application system / Ainul Azila Che Fauzi, Nur Izzah Mohd Ab Ghani and Auni Fauzi - Che Fauzi, Ainul Azila; Mohd Ab Ghani, Nur Izzah; Fauzi, Auni (Universiti Teknologi MARA, Kelantan, 2023)
Any democracy must have an open voting process that satisfies the demands of the populace in order to assign power to the most qualified candidate. A fair and transparent election system is essential to the freedom that the majority of people in today's world enjoy. In every nation, voting is an important and serious occasion. However, the traditional elections are controlled and managed by a centralised authority, which makes them vulnerable to numerous security privacy, fraud, integrity, and fairness issues. On the other hand, electronic voting offers less errors and quicker counting. It can also remove votes that are questioned or declared invalid. Currently, the election system used by Universiti Teknologi Mara Cawangan Kelantan (UiTMCK) is suffering from a poor voter turnout since the system in place is not convenient for most students. Normally, the students would have to stand in a long queue to register when joining a voting event. As the registration of the students is recorded manually, it is difficult for the event organizer to manage the event efficiently. It is also unable to prevent any irresponsible authorities who may exploit and manipulate the votes in favor of their preferred candidates which temper the expected free and fair elections. Therefore, E-Voting Mobile Application System (E-Voting MAS) is proposed to overcome these problems. E-Voting MAS was developed using Agile model. This study proves the E-Voting MAS is feasible at UiTMCK, utilizing an approach that seamlessly integrates convenience and security.